Detection of endo-epicardial atrial low-voltage areas using unipolar and omnipolar voltage mapping - Van Schie, Mathijs S.; Knops, Paul; Zhang, Lu; Van Schaagen, Frank R. N.; Taverne, Yannick J. H. J.; De Groot, Natasja M. S. (Frontiers in Physiology, 2022)
Background: Low-voltage areas (LVA) can be located exclusively at either the endocardium or epicardium. This has only been demonstrated for bipolar voltages, but the value of unipolar and omnipolar voltages recorded from either the endocardium and epicardium in predicting LVAs at the opposite layer remains unknown. The goal of this study was therefore to compare simultaneously recorded endo-epicardial unipolar and omnipolar potentials and to determine whether their voltage characteristics are predictive for opposite LVAs. Methods: Intra-operative simultaneous endo-epicardial mapping (256 electrodes, interelectrode distances 2mm) was performed during sinus rhythm at the right atrium in 93 patients (67±9 years, 73 male). Cliques of 4 electrodes (2x2 mm) were used to define maximal omnipolar (Vomni,max) and unipolar (Vuni,max) voltages. LVAs were defined as Vomni,max ≤0.5 mV or Vuni,max ≤1.0 mV. Results: The majority of both unipolar and omnipolar LVAs were located at only the endocardium (74.2% and 82.0% respectively) or epicardium (52.7% and 47.6% respectively). Of the endocardial unipolar LVAs, 25.8% were also located at the opposite layer and 47.3% vice-versa. In omnipolar LVAs, 18.0% of the endocardial LVAs were also located at the epicardium and 52.4% vice-versa. The combination of epicardial Vuni,max and Vomni,max was most accurate in identifying dual-layer LVAs (50.4%). Conclusions: Unipolar and omnipolar LVAs are frequently located exclusively at either the endocardium or epicardium. Endo-epicardial LVAs are most accurately identified using combined epicardial unipolar and omnipolar voltages. Therefore, a combined endo-epicardial unipolar and omnipolar mapping approach is favoured as it may be more indicative of possible arrhythmogenic substrates.